Observation of the asphericity of 4f-electron density and its relation to the magnetic anisotropy axis in single-molecule magnets - Gao, Chen; Genoni, Alessandro; Gao, Song; Jiang, Shangda; Soncini, Alessandro; Overgaard, Jacob (Nature chemistry, 2020)
The distribution of electrons in the 4f orbitals of lanthanide ions is often assigned a crucial role in the design of single-molecule magnets, which maintain magnetization in zero external field. Optimal spatial complementarity between the 4f-electron density and the ligand field is key to maximizing magnetic anisotropy, which is an important factor in the ability of lanthanide complexes to display single-molecule magnet behaviour. Here we have experimentally determined the electron density distribution in two dysprosium molecular complexes by interpreting high-resolution synchrotron X-ray diffraction with a multipole model. The ground-state 4f-electron density is found to be an oblate ellipsoid, as is often deduced from a simplified Sievers model that assumes a pure |±15/2> ground-state doublet for the lanthanide ion. The large equatorial asymmetry-determined by a model wavefunction-was found to contain considerable M mixing of |±11/2> and only 81% of |±15/2>. The experimental molecular magnetic easy axes were recovered, and found to deviate by 13.1° and 8.7° from those obtained by ab initio calculations.